2020
DOI: 10.1021/acs.jmedchem.9b01681
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of Novel Pyrazolopyrimidines as Potent and Orally Bioavailable Allosteric HIV-1 Integrase Inhibitors

Abstract: The standard of care for HIV-1 infection, highly active antiretroviral therapy (HAART), combines two or more drugs from at least two classes. Even with the success of HAART, new drugs with novel mechanisms are needed to combat viral resistance, improve adherence, and mitigate toxicities. Active site inhibitors of HIV-1 integrase are clinically validated for the treatment of HIV-1 infection.Here we describe allosteric inhibitors of HIV-1 integrase that bind to the LEDGF/p75 interaction site and disrupt the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Li et al reported an approach using large quantities of the starting materials 47a and 18 obtaining a dihydro derivative (not shown). Subsequently, the authors achieved an oxidation with DDQ without an intermediate purification step involved, to produce the unsaturated product 49 in 64% yield ( Scheme 16 a) [ 55 ].…”
Section: Synthesis and Functionalizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Li et al reported an approach using large quantities of the starting materials 47a and 18 obtaining a dihydro derivative (not shown). Subsequently, the authors achieved an oxidation with DDQ without an intermediate purification step involved, to produce the unsaturated product 49 in 64% yield ( Scheme 16 a) [ 55 ].…”
Section: Synthesis and Functionalizationmentioning
confidence: 99%
“…The reaction results are widely employed in medicinal chemistry because it allows modifications with various structural motifs at electrophilic positions of the pyrimidine ring. Recently, it has been employed with the aim of adding aromatic amines [ 34 , 67 ], alkylamines [ 48 , 76 ], cycloalkylamines [ 55 , 77 , 78 ], and substituted alkoxides [ 67 ]. In this respect, McNally, Paton, and co-workers designed an interesting way of coupling the 5-(diphenylphosphanyl)pyridine 118 to the position 7 of the fused pyrazole PP , generating the phosphonium salt 119 according to the authors [ 79 ].…”
Section: Synthesis and Functionalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Another class of integrase inhibitors, the allosteric inhibitors (ALLINIs) (Figure 1B) target the pocket normally occupied by the integrase-binding domain (IBD) of the lens epithelium-derived growth factor (LEDGF/p75)(36-39) (Figure 1C). LEDGF binds to IN and directs the IN-cDNA complex toward transcriptionally active areas of the genome for integration(40-42).…”
Section: Introductionmentioning
confidence: 99%